Transmission through aluminum of beta particles emitted by infinitely-thick sources - Rodríguez Pasqués, R. H.; Mullen, P. A.; George, G. A.; Harding, J. E. (Elsevier BV, 1967)
Fil: Rodríguez Pasqués, R. H. Comisión Nacional de Energía Atómica; Argentina